2023
DOI: 10.1002/mar.21801
|View full text |Cite
|
Sign up to set email alerts
|

The impact of financial scarcity on green consumption: Sequential mediating effects of anxiety and self‐efficacy

Abstract: There is a consensus to promote green consumption to drive sustainable human development and high-quality economic development. It is therefore essential for academics, policymakers, and marketers to understand the factors that influence green consumption. Through four experiments, this study examines the effect of financial scarcity-a feeling commonly experienced by consumers-on green consumption. These experiments show that financial scarcity can hinder consumers' choice of green products. The above process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…We argue in the present context that thinking about local consump- First, past research has shown that anticipated warm glow underlies judgments and decisions in the context of ethical and environmentally-friendly consumption (Andrews et al, 2014;Giebelhausen et al, 2016). For example, it has been shown that anticipated warm glow arising from cause marketing (Andrews et al, 2014), bundling hedonic products with charity donations (Strahilevitz & Myers, 1998), and purchasing products with ethical attributes (e.g., Bezençon et al, 2020) (Cannon et al, 2019;Han et al, 2023;Lee & Shrum, 2012;Mandel et al, 2017;Zhang, Ma, et al, 2023). A key finding in this literature is that people are motivated to compensate for self-discrepancy by engaging in activities that help them reduce the psychological discomfort associated with the discrepancy.…”
Section: Perceived Control and Likelihood Of Local Consumptionmentioning
confidence: 88%
See 2 more Smart Citations
“…We argue in the present context that thinking about local consump- First, past research has shown that anticipated warm glow underlies judgments and decisions in the context of ethical and environmentally-friendly consumption (Andrews et al, 2014;Giebelhausen et al, 2016). For example, it has been shown that anticipated warm glow arising from cause marketing (Andrews et al, 2014), bundling hedonic products with charity donations (Strahilevitz & Myers, 1998), and purchasing products with ethical attributes (e.g., Bezençon et al, 2020) (Cannon et al, 2019;Han et al, 2023;Lee & Shrum, 2012;Mandel et al, 2017;Zhang, Ma, et al, 2023). A key finding in this literature is that people are motivated to compensate for self-discrepancy by engaging in activities that help them reduce the psychological discomfort associated with the discrepancy.…”
Section: Perceived Control and Likelihood Of Local Consumptionmentioning
confidence: 88%
“…However, prior research has not considered the possibility that consumer self‐discrepancy, i.e., the gap between consumers' actual and ideal states, could influence the likelihood of local consumption. Prior research has shown that different types of self‐discrepancies, such as resource scarcity, lack of power, lack of control, or low sense of intelligence can influence consumption behavior (Kim & Rucker, 2012; Mandel et al, 2017; Rucker & Galinsky, 2008; Sharma & Alter, 2012; Zhang, Ma, et al, 2023). We extend these findings by showing for the first time that self‐discrepancy in the form of loss of control can influence consumer preference for local consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that price has been defined not only in economic terms but also in terms of the value and desirability of a specific good or service, again referring to the importance of green motivation, which has been discussed in the first section of the present review [99]. It has been shown that, along with price, other factors, i.e., green product quality, the focus on the environmental benefits of such a product [97] and financial scarcity [100], play a major role in consumers' buying behaviors. Altogether, lower prices, higher perceived product quality and environmental benefit, and the availability of adequate economic resources are associated with greater sustainable product purchase decisions [97,100].…”
Section: Contextual Factorsmentioning
confidence: 99%
“…It has been shown that, along with price, other factors, i.e., green product quality, the focus on the environmental benefits of such a product [97] and financial scarcity [100], play a major role in consumers' buying behaviors. Altogether, lower prices, higher perceived product quality and environmental benefit, and the availability of adequate economic resources are associated with greater sustainable product purchase decisions [97,100].…”
Section: Contextual Factorsmentioning
confidence: 99%